Re-Mapping dan Evaluasi Alat Pemadam Api Ringan (APAR) di PT. X Mojoagung - Asvinia Ananta Zulatuva; Achmad Syafiuddin; Bakhtiar, Bakhtiar (Yayasan Literasi Sains Indonesia, 2023)
Re-MAPPING of APAR at PT X Mojoagung in buildings 1 and 2 has been carried out. The re-MAPPING aims to evaluate the number and type of fire extinguishers in building 1, non-woven mask production room and building 2, infusion production room. This re-MPPING and evaluation is carried out in accordance with the regulations in PERMENAKERTRANS RI No. 04 of 1980 and NFPA 10 of 2013, to fulfill life safety guarantees in accordance with applicable K3 rules. The benefits of this research are that it can be an additional reference regarding the evaluation and consequences of fire extinguishers, providing fire prevention and control at Factory X Mojoagung as a preparedness in the event of a fire disaster and as input for implementing the correct placement of fire extinguishers and in accordance with the provisions at Factory X Mojoagung.The data obtained is then evaluated based on the rules used. The results of the data evaluation showed that the number of fire extinguishers in PT X Mojoagung in buildings 1 and 2 corresponded to a total of 30 fire extinguishers. The amount and type of contents in each fire extinguisher is in accordance with the level of hazard that occurs in each building.